VITAMIN AND MINERAL SUBSTANCE PROVISION FOR THE CHILDREN, SUFFERING FROM THE ALLERGIES IN MODERN CONDITIONS - I.A. Gromov; L.S. Namazova; R.M. Torshkhoeva; T.E. Borovik; T.N. Stepanova; S.G. Makarova; V.A. Skvortsova (Union of pediatricians of Russia, 2008)
(Педиатрическая фармакология. - 2008;5(3):76-81)